2006
DOI: 10.1021/bi060212u
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity and Inhibition of Human Histone Deacetylase 8 Is Dependent on the Identity of the Active Site Metal Ion

Abstract: Histone deacetylases play a key role in regulating transcription and other cellular processes by catalyzing the hydrolysis of epsilon-acetyl-lysine residues. For this reason, inhibitors of histone deacetylases are potential targets for the treatment of cancer. A subset of these enzymes has previously been shown to require divalent metal ions for catalysis. Here we demonstrate that histone deacetylase 8 (HDAC8) is catalytically active with a number of divalent metal ions in a 1:1 stoichiometry with the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
251
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(270 citation statements)
references
References 65 publications
16
251
3
Order By: Relevance
“…The deacetylase reaction requires a transition metal ion and, although the HDACs are typically considered Zn 2+ -containing enzymes, the metal ion in the active site, as demonstrated by the X-ray structure of HDAC8, can be substituted by Fe 2+ , Co 2+ and Mn 2+ [244]. This is consistent with the hypothesis that HDAC8 could function as a Fe 2+ -catalyzing enzyme in vivo ( Table 1) [245]. The overall fold of other recently crystallized HDACs is similar to the previously reported structures, even if several key features distinguish the various classes.…”
Section: Class I Ii and Iv Deacetylasessupporting
confidence: 78%
“…The deacetylase reaction requires a transition metal ion and, although the HDACs are typically considered Zn 2+ -containing enzymes, the metal ion in the active site, as demonstrated by the X-ray structure of HDAC8, can be substituted by Fe 2+ , Co 2+ and Mn 2+ [244]. This is consistent with the hypothesis that HDAC8 could function as a Fe 2+ -catalyzing enzyme in vivo ( Table 1) [245]. The overall fold of other recently crystallized HDACs is similar to the previously reported structures, even if several key features distinguish the various classes.…”
Section: Class I Ii and Iv Deacetylasessupporting
confidence: 78%
“…An alternative twostate ensemble model for binding was also used to assess catalytic efficacy ( Figure S2), which agreed qualitatively with the current simple model for a reasonable range of binding affinities. This model qualitatively predicts the trend seen in catalytic activity for these metals in experiment, though the trend is slightly perturbed, 37 either due to experimental errors or inaccuracies of our model. Co 2+ is predicted as the most active, followed by Zn 2+ and Fe 2+ .…”
Section: +supporting
confidence: 57%
“…Class I, II, and IV HDACs share a similar catalytic mechanism that involves the coordination of a divalent metal ion. Initial studies suggested that the catalytic metal was Zn(II), but recent findings have indicated that Fe(II) may play a more significant role (86). Regardless of the nature of the divalent ion, mechanistic studies indicate that the enzyme-coordinated metal and a conserved tyrosine (for Class I, IIb, and IV) or histidine (Class IIa) polarizes the carbonyl oxygen, priming the carbonyl carbon of the acetyl group.…”
Section: B Histone Acetylationmentioning
confidence: 99%